Implementation of Assessment Standards Based on Learners’ Needs at PKBM Cahaya Ilmu Pekanbaru - Rafael Chasyanova; Rahmat Fahmi (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study aims to analyze the implementation of needs-based assessment standards for learners at the Cahaya Ilmu Community Learning Center (PKBM) in Pekanbaru. The approach used was qualitative, with data collection methods through observation, interviews, and questionnaires involving tutors, administrators, and learners. The results showed that the implementation of assessment standards in PKBM was carried out flexibly and contextually, adapting to the diverse characteristics and needs of learners. Needs identification was carried out through initial assessments, observations, group discussions, and grouping of learners' abilities. The form of assessment not only focused on cognitive aspects but also included skills and attitudes through direct practice, portfolios, and authentic assessments. In addition, learners were involved in the assessment process through self-reflection and active participation in learning activities. However, in its implementation, there were still obstacles such as limited facilities and infrastructure, tutor competency, and variations in learners' learning motivations. Therefore, it is necessary to strengthen the capacity of tutors and develop more effective assessment instruments so that assessment standards can support the improvement of learning quality and empower learners optimally.